Watou Poëziezomer 2006 : Extiem. - Haerynck, Maria; Declercq, Joost; Mandelinck, Gwy; Van Synghel, Koen (Deurle ; Watou : MDD (museum Dhondt-Dhaenens) Deurle : vzw Poëziezomers-Kunstzomers Watou, 2006)
Antich, Carolina ; Araki, Nobuyoshi ; Arion, Frank Martinus ; Brenner, Birgit ; Chiasera, Paolo ; Claerbout, David ; Clark, Larry ; Devriendt, Robert ; Dujourie, Lili ; Eisinga, Jeroen ; Emin, Tracey ; Eussen, Anneke ; Vanden Eynde, Charlotte ; Fabre, Jan ; François, Michel ; Goethals, Marc ; Hers, François ; de Jong, Folkert ; Lipski, Edward ; Lizene, Jacques ; Mees, Guy ; van Muiswinkel, Wineke ; Rogiers, Peter ; Rudelius, Julika ; Sandison, Charles ; De Sauter, Willy ; Templeton, Ed ; Tillmans, Wolfgang ; Timmermans, Ante ; Vercruysse, Jan ; Verkerk, Emo ; van Zyl, Ina
Frans
Nederlands
Exhibition. Watou Poëziezomer 2006 : Extiem. Watou. vzw Poëziezomers-Kunstzomers Watou. 2006-07-02. 2006-09-10
boek